Repositioning the Indonesian Halal Industry in the Global Value Chain: Halal Certification, International Standardization, and Islamic Values - Raden Nurhayati; Fauzia Assilmy (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study examines the repositioning of Indonesia’s halal industry in the Global Value Chain through the analysis of halal certification, international standardization, and Islamic economic values. The study is motivated by Indonesia’s significant potential as a country with a large Muslim market and continuously developing halal ecosystem, which has not yet been fully reflected in its position within the global halal value chain. Indonesia still faces several challenges, including international recognition of halal certification, harmonization of standards, halal logistics readiness, product traceability, Islamic financing, and the capacity of MSMEs to enter global markets. This research uses a descriptive qualitative method using a library research approach and content analysis. The findings indicate that halal certification should be positioned as an instrument of trust, quality assurance, and international market access. International standardization is necessary to ensure that Indonesian halal products receive cross-border recognition and are not constrained by regulatory differences. Meanwhile, Islamic economic values such as halal, tayyib, trustworthiness, justice, transparency, and maṣlaḥah serve as normative foundations so that halal industry development is not only directed toward competitiveness, but also toward consumer protection and public benefit.